Astragalus Polysaccharide Reduces Blood Pressure, Renal Damage, and Dysfunction Through the TGF-β1-ILK Pathway - Zheng, Wei; Huang, Tao; Tang, Qi-Zhen; Li, Shi; Qin, Jie; Chen, Feng (Frontiers in Pharmacology, 2021)
Background:Astragalus polysaccharide extract (APS) has been shown to exhibit antioxidant and anti-inflammatory potential in the treatment of several diseases. However, whether APS could protect against renal damage in hypertensive mice is unknown. Methods: Hematoxylin and eosin staining, immunohistochemistry, real-time polymerase chain reaction, and Western blotting were used to investigate the effect of APS on the renal damage in deoxycorticosterone acetate- (DOCA) salt- and angiotensin II- (Ang II-) induced hypertensive mice and to elucidate the underlying mechanisms. Results: Our data demonstrated that APS significantly reduced blood pressure in DOCA-salt- and Ang II-treated mice. Furthermore, APS reduced the inflammatory response and renal fibrosis, thereby improving renal function. Furthermore, the levels of serum creatinine, urea nitrogen, and uric acid increased in DOCA-salt-treated mice, alleviated by APS administration. At the molecular level, DOCA-salt and Ang II increased the mRNA levels of IL-1β, IL-6, α-SMA, collagen I, and collagen III, while APS significantly inhibited these effects. APS inhibited the TGF-β1/ILK signaling pathway, which was activated in hypertensive mice due to the administration of DOCA-salt. Conclusion: Our results suggest that APS plays a beneficial role in improving renal dysfunction in hypertensive mice.